Indonesia's Agriculture Tax: An Approach to the GTAP Model - Diah Setyawati Dewanti; Fitra Prasapawidya Purna (Universitas Negeri Malang, 2022)
Tax is a policy tool to control the market. As Indonesia implied an agriculture tax of about 10% in 2014, it is worthy of capturing how it affects the market. This paper aims to find the effect of the implied tax on the market by seeing the country's sales, demand, imports, exports, and welfare. The method used is GTAP model simulation with the base of GTAP9 and aggregated based on the case applied. The result shows that the tax implied makes the demand, import, and export decrease even for the country that implements it. However, the sale and welfare gained by the origin country are increasing. Even China, the United States, and Australia have difficulty dealing with the policy as their welfare decreases. This research tries to find the effect of the agriculture tax that Indonesia implied in 2014. Using GTAP model simulation reveals how the tax affects the sale, demand, import, export, and gain or loss of welfare country.